Thermal Effects Induced in Liver Tissues by Pulsed Focused Ultrasonic Beams from Annular Array Transducer - Tamara KUJAWSKA; Wojciech SECOMSKI; Kazimierz KRAWCZYK; Andrzej NOWICKI (Archives of Acoustics, 2013)
Many therapeutic applications of pulsed focused ultrasound are based on heating of detected lesions which may be localized in tissues at different depths under the skin. In order to concentrate the acoustic energy inside tissues at desired depths a new approach using a planar multi-element annular array transducer with an electronically adjusted time-delay of excitation of its elements, was proposed. The 7-elements annular array transducer with 2.4 MHz center operating frequency and 20 mm outer diameter was produced. All its elements (central disc and 6 rings) had the same radiating area. The main purpose of this study was to investigate thermal fields induced in bovine liver in vitro by pulsed focused ultrasonic beams with various acoustic properties and electronically steered focal plane generated from the annular array transducer used. The measurements were performed for the radiating beams with the 20 mm focal depth. In order to maximize nonlinear effects introducing the important local temperature rise, the measurements have been performed in two-layer media comprising of a water layer, whose thickness was specific for the transducer used and equal to 13 mm, and the second layer of a bovine liver with a thickness of 20 mm. The thickness of the water layer was determined numerically as the axial distance where the amplitude of the second harmonics started to increase rapidly. The measurements of the temperature rise versus time were performed using a thermocouple placed inside the liver at the focus of the beam. The temperature rise induced in the bovine liver in vitro by beams with the average acoustic power of 1W, 2Wand 3Wand duty cycle of 1/5, 1/15 and 1/30, respectively, have been measured. For each beam used the exposure time needed for the local tissue heating to the temperature of 43◦C (used in therapies based on ultrasonic enhancement of drug delivery or in therapies involving stimulation of immune system by enhancement of the heat shock proteins expression) and to the temperature of 56◦C (used in HIFU therapies) was determined. Two sets of measurements were done for each beam considered. First, the thermocouple measurement of the temperature rise was done and next, the real-time monitoring of dynamics of growth of the necrosis area by using ultrasonic imaging technique, while the sample was exposed to the same acoustic beam. It was found that the necrosis area becomes visible in the ultrasonic image only for beams with the average acoustic power of 3 W, although after cutting the sample the thermo ablated area was visible with the naked eye even for the beams with lower acoustic power. The quantitative analysis of the obtained results allowed to determine the exposure time needed to get the necrosis area visible in the ultrasonic image.